2010
DOI: 10.1111/j.1461-0248.2010.01521.x
|View full text |Cite
|
Sign up to set email alerts
|

Key innovations within a geographical context in flowering plants: towards resolving Darwin’s abominable mystery

Abstract: Elucidating factors associated with diversification have been attempted in lineages as diverse as birds, mammals and angiosperms, yet has met with limited success. In flowering plants, the ambiguity of associations between traits and diversification has sparked debate since Darwin's description of angiosperm diversification as an 'abominable mystery'. Recent work has found that diversification is often diversity-dependent, suggesting that species richness depends on geographical area available more than on tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 53 publications
3
108
0
Order By: Relevance
“…(c) Estimation of species area relationships We used published data on the global geographical extent of plant families ( [20,26], see the electronic supplementary material, table S1). We used these plant family range values with gall-inducing midge species richness in multivariate generalized linear models with plant insularity and plantlineage age to control for the influence of other factors.…”
Section: Methodsmentioning
confidence: 99%
“…(c) Estimation of species area relationships We used published data on the global geographical extent of plant families ( [20,26], see the electronic supplementary material, table S1). We used these plant family range values with gall-inducing midge species richness in multivariate generalized linear models with plant insularity and plantlineage age to control for the influence of other factors.…”
Section: Methodsmentioning
confidence: 99%
“…To date, results have been mixed, for example, Cardillo et al [72,73] and Ricklefs [74] reported faster rates of diversification at lower latitude in birds, but Wiens et al [75] [77,78]. Area by far explains the most variation in diversification models for plants [79][80][81], but significant additional variation in rates is explained by environmental energy [80,82].…”
Section: Diversity and Diversificationmentioning
confidence: 99%
“…This model underscores the potential importance of gene loss in the evolution of ecologically important traits. E volution of flower symmetry is tightly correlated with pollinator shifts and has been proposed as a key innovation within the angiosperms (1)(2)(3)(4)(5)(6). In the plantain family (Plantaginaceae, Lamiales), morphological and phylogenetic analyses suggest that the ancestral flower was five-parted, bilaterally symmetrical (monosymmetrical and zygomorphic), and insect-pollinated (7,8).…”
mentioning
confidence: 99%